2014
DOI: 10.1038/mi.2013.108
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic macrophages impair autophagy in epithelial cells through Wnt1: relevance in IBD

Abstract: A defective induction of epithelial autophagy may have a role in the pathogenesis of inflammatory bowel diseases. This process is regulated mainly by extracellular factors such as nutrients and growth factors and is highly induced by diverse situations of stress. We hypothesized that epithelial autophagy is regulated by the immune response that in turn is modulated by local hypoxia and inflammatory signals present in the inflamed mucosa. Our results reveal that HIF-1α and Wnt1 were co-localized with CD68 in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 44 publications
3
62
0
Order By: Relevance
“…In line with recent studies linking deficient autophagy with IBD 22, 45, 46 , DSS-treated WT mice and Il-10 −/− mice presented accumulation of phosphorylated/activated mTOR, the main inhibitor of autophagy, and the autophagy protein p62, together with increased NF-κB phosphorylation and inflammatory gene expression. Hypoxia restored autophagy clearance of p62 reducing mTOR phosphorylation and proinflammatory gene expressionand signaling inthese mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with recent studies linking deficient autophagy with IBD 22, 45, 46 , DSS-treated WT mice and Il-10 −/− mice presented accumulation of phosphorylated/activated mTOR, the main inhibitor of autophagy, and the autophagy protein p62, together with increased NF-κB phosphorylation and inflammatory gene expression. Hypoxia restored autophagy clearance of p62 reducing mTOR phosphorylation and proinflammatory gene expressionand signaling inthese mice.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the amount of membrane-bound LC3-II provides a good index of autophagy induction 20 . Environmental stress induces autophagy through the inhibition of mammalian target of rapamycin (mTOR), a serine/threonine protein kinase that belongs to the phosphatidylinositol 3-kinase-related kinase family 21, 22 . Hypoxia inhibits mTOR signaling through HIF-1-dependent and -independent mechanisms, as well as through proteins that prevent the binding of mTOR with the mTOR upstream activator Ras homolog enriched in brain (RHEB) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Wnt1 in macrophages initiated a Wnt signaling cascade in epithelial cells, resulting in activation of mTOR and inhibition of autophagy. 69 These results demonstrate how an environmental stress characteristic of IBD can result in intercellular signaling cascades that inhibit autophagy in epithelial cells, resulting in loss of function of the epithelial barrier. ER stress is high at baseline in a number of secretory cell types in the intestinal epithelium, including Paneth cells and goblet cells, 70 and has been implicated as a cause of intestinal inflammation in mouse studies of Xbp1, 71 In a recent study examining the regulation of the ER stress response, loss of the unfolded protein response and loss of autophagy were shown to reciprocally engage one another.…”
Section: Autophagy In the Maintenance Of Intestinal Homeostasismentioning
confidence: 72%
“…Hypoxic mucosal macrophages from IBD patients exhibit increased HIF-1 and Wnt1 expression, and coculture models revealed that macrophage-derived Wnt1 can activate mTOR and inhibit autophagy in IECs (120). Mucosa-associated microbiota are likely also prominent modulators of potential hypoxia-elicited autophagic responses (see Figure 2).…”
Section: Metabolic Regulation Of Epithelial Autophagymentioning
confidence: 99%